Effects of Physiological Levels of the Green Tea Extract Epigallocatechin-3-Gallate on Breast Cancer Cells - Zeng, Li; Holly, Jeff M. P.; Perks, Claire M. (Frontiers in Endocrinology, 2014)
Physiological concentrations of the green tea extract EGCG caused growth inhibition in oestrogen receptor α (ERα)-positive MCF7 cells, that was associated with down-regulation of the ERα and reduced insulin-like growth factor (IGF) binding protein-2 (IGFBP-2) abundance and increased protein abundance of the tumour suppressor genes p53/p21. In contrast to MCF7 cells that have wt p53, EGCG alone did not change cell proliferation or death significantly in another ERα-positive cell line T47D that possesses mutant p53. EGCG increased ERα protein levels and as a consequence, the cells responded significantly better to an ERα antagonist Tamoxifen (TAM)) in the presence of EGCG. EGCG significantly increased cell death in an ERα-negative cell line, MDA-MB-231 that also possesses mutant p53. EGCG significantly increased the ERα and IGF-I receptor (IGF-IR) levels and thereby enhanced the sensitivities of the cells to Tamoxifen and a blocking antibody targeting the IGF-1R (αIR3). In contrast to MCF7, T47D and MDA-MB-231 breast cancer cells that exhibited significant changes in key molecules involved in breast growth and survival upon treatment with physiological levels of EGCG, the growth, survival and levels of these proteins in non-malignant breast epithelial cells, MCF10A cells, were not affected.